The Role of Social Media Marketing in Enhancing Customer Citizenship Behaviour: The Mediating Effect of Brand Loyalty in Cement Industry (Manado) - Jessica Stevanie Tumonggor; Lilly Linne Kainde (Economics and Digital Business Review, 2026)
This study investigates the role of Social Media Marketing (SMM) in enhancing Customer Citizenship Behaviour (CCB) in the cement industry, focusing on a regional market in Manado. The research is motivated by the growing importance of social media as a platform for technical communication, relationship building, and stakeholder engagement, particularly in construction-related industries where product reliability and trust are critical. Although previous studies have highlighted the benefits of digital engagement, limited research has examined how SMM influences voluntary customer behaviours through the mediating role of Brand Loyalty (BL). Using a quantitative descriptive correlational, data were collected from 300 respondents through a online questionnaire. Validity and reliability tests confirmed that all measurement indicators met statistical criteria. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and SPSS to test both direct and mediating effects indicated strong and significant relationships among variables. The findings reveal that SMM has a positive effect on both BL and CCB. Mediation testing findings that BL partially mediates the relationship between SMM and CCB, indicating that SMM encourages voluntary supportive behaviours both directly and indirectly by strengthening customer loyalty. This study contributes to the literature by providing empirical evidence from an industrial, region-specific context and highlights the strategic role of digital communication in fostering customer advocacy, feedback, helping behaviour, and tolerance. These insights underscore the importance for industrial brands to invest in consistent, interactive, and value-oriented social media strategies to enhance long-term customer engagement and support.